The impact of the micro-scale movement restriction (PPKM micro) policy on the mobility of people and the trend of daily cases of COVID-19 in the Special Region of Yogyakarta - Puspitarani, Fitriana; Nur Hayati (BKM Public Health and Community Medicine, 2021)
Purpose: This article aims to examine the impact of the micro-scale Community Activity Restriction (PPKM) policy implemented by the Yogyakarta Special Region Government on community mobility and the trend of COVID-19 cases from February 9, 2021, to March 23, 2021. Method: Method Exploratory DataAnalysis (EDA) is used to analyze and report the Micro PPKM policy’s impact on mobility and the trend of daily confirmation cases in the Special Region of Yogyakarta Province. The data used include data on daily confirmed cases of COVID-19 from the Health Office of the Special Region of Yogyakarta, trends in community mobility during the COVID-19 pandemic from the Google COVID-19 Community Mobility Report from February 9, 2021, to March 23, 2021. Result: Google COVID, The Community Mobile Report, shows that there is an 18% decrease in the mobility of the people of the Special Region of Yogyakarta for visits to retail and recreation, a 19% decrease in mobility in parks, a 31% decrease in mobility in public transportation centers, a 26% decrease in mobility at work, and an increase in 6% mobility in settlements. The trend of daily cases during the implementation of micro PPKM tends to be stable (<1%), with an average daily case of 0.6%. Through the results of observations of data from two different sources, explaining that the level of community mobility in the Special Region of Yogyakarta was lower when the Micro-scale Community Activity Restrictions (PPKM) was implemented. There was an emphasis on daily confirmed cases of COVID-19 in the Special Province of Yogyakarta. Conclusion: The micro PPKM policy is expected to be maintained in handling COVID-19 until cases can be controlled. At least the decrease in cases cannot be used as a supporting reference. Further analysis is needed to see the factors that influence the trend of daily confirmed cases in the Special Region of Yogyakarta Province. Tujuan: Artikel ini bertujuan untuk mengkaji dampak kebijakan Pemberlakukan Pembatasan Kegiatan Masyarakat (PPKM) berskala mikro yang diterapkan oleh Pemerintah Provinsi Daerah Istimewa Yogyakarta terhadap mobilitas masyarakat dan tren kasus harian COVID-19 sejak 9 Februari 2021 hingga 23 Maret 2021. Metode: Metode Exploratory Data Analysis (EDA) digunakan untuk menganalisis dan melaporkan dampak kebijakan PPKM Mikro yang diterapkan terhadap mobilitas masyarakat dan tren kasus konfirmasi harian di Provinsi Daerah Istimewa Yogyakarta. Data yang digunakan antara lain data kasus konfirmasi harian COVID-19 dari Dinas Kesehatan Provinsi Daerah Istimewa Yogyakarta, tren mobilitas masyarakat selama pandemi COVID-19 dari Google COVID-19 Community Mobility Report sejak tanggal 9 Februari 2021 hingga 23 Maret 2021. Hasil: Google COVID-19 Community Mobile Report menunjukkan bahwa terdapat penurunan 18% mobilitas masyarakat Provinsi Daerah Istimewa Yogyakarta untuk kunjungan ke retail dan rekreasi, penurunan 19% mobilitas di taman, penurunan 31% mobilitas di pusat transportasi umum, penurunan 26% mobilitas di tempat kerja, dan peningkatan 6% mobilitas di pemukiman. Tren kasus harian selama pelaksanaan PPKM mikro cenderung stabil (<1%) dengan rata-rata kasus harian sebesar 0,6%. Melalui hasil observasi terhadap data dari dua sumber yang berbeda, dapat dijelaskan bahwa tingkat mobilitas masyarakat di Provinsi Daerah Istimewa Yogyakarta lebih rendah pada saat dilaksanakan Pemberlakukan Pembatasan Kegiatan Masyarakat (PPKM) skala mikro dan adanya penekanan kasus konfirmasi harian COVID-19 di Provinsi Daerah Istimewa Yogyakarta. Kesimpulan: Pemberlakuan kebijakan PPKM mikro diharapkan dapat terus dipertahankan dalam penanganan COVID-19 hingga kasus dapat dikendalikan. Sedikitnya penurunan kasus tidak dapat dijadikan acuan pendukung, diperlukan analisis lanjutan untuk melihat faktor yang mempengaruhi tren kasus konfirmasi harian di Provinsi Daerah Istimewa Yogyakarta.